Analisis dan Perancangan Sistem Informasi Pembayaran Pajak Air Permukaan Pada Badan Keuangan Daerah Berbasis Web - Zulfi Karman; Chandy Ophelia S; Siska Nurul Marwiyah; Suyanti (STMIK Budi Darma, 2023)
Badan Keuangan Daerah Provinsi Jambi office that receives surface water tax payments. Surface water tax is a tax on the extraction or use of surface water. Currently, the Regional Financial Agency of Jambi Province has not used an information system effectively for processing surface water tax payments, where company data, payment data and reports are still recorded in the ledger, and after that the data is transferred to Microsoft Office Excel for report generation. This is very vulnerable to human error such as loss of data and also requires a long time to complete reports.Consequently , it is necessary to design a website-based surface water tax payment information system at the Regional Financial Agency of Jambi Province. This system was built using the waterfall model as a system development method, where in its creation we carry out it step by step and proceed sequentially. System development tools use UML (Unified Modeling Language) to describe object-based analysis and modeling. The UML used includes use case diagrams, class diagrams and activity diagrams and uses the PHP programming language. The output of this research is a prototype design for a website-based analysis and design system for surface water tax payment information at the Regional Financial Agency of Jambi Province. Further research can be completed with other data management